Rancang Bangun Sistem Informasi Penjualan Perabotan Pada CV. Evamas - Irani Yuni Mora Napitupulu; Sri Muryani (LPPM Universitas Bina Sarana Informatika, 2018)
Sales information system is a system that processes data and transactions of the entire business activities consisting of the sale of goods or services. With the advancement of technology, demands the importance of information in every company so that information can be obtained quickly, precisely and accurately. The existence of a computerized system is expected to help all the difficult work done to be easy to do in order to get good results from before. In connection with that, according to the author on CV. Evamas requires the existence of an information system that supports and provide satisfactory service for the customer. For this research, the author discusses the furniture sales information system on the CV. Evamas that has not been computerized. The system contained in the CV. Evamas is still done manually, ranging from sales procedures, payment procedures and reporting procedures. Computerized system is the best solution to solve the problems that exist in the CV. Evamas. Therefore, with the design of a computerized system better than the manual system to run more effectively and efficiently so that the sales process in the store better than the previous system.